Clubbing in patients with fibrotic interstitial lung diseases. (November 2017) - van Manen, M.J.G.; Vermeer, L.C.; Moor, C.C.; Vrijenhoeff, R.; Grutters, J.C.; Veltkamp, M.; Wijsenbeek, M.S.
Abstract: Background: Clubbing is associated with poor prognosis and is variably present in patients with idiopathic pulmonary fibrosis (IPF), but is also seen in other fibrotic interstitial lung diseases (ILDs). Little is known about the best methodology to assess clubbing in ILDs and, hence, the prevalence and clinical utility and clinical significance of clubbing. We therefore aimed to evaluate the agreement between different clubbing assessment methods in patients with fibrotic ILDs. Additionally, we assessed the prevalence of clubbing in different fibrotic ILDs and related clubbing to disease severity and quality of life. Methods: Consecutive outpatients with fibrotic ILDs of two tertiary referral centers were included. Clubbing was assessed with the phalangeal depth ratio, the digital index, the Schamroth sign test, and by the treating physicians and investigator. Results: We included 153 patients (100 men), mean age 65 (range 33–88), mean FVC 79% (25–145%), mean TLCOc 50% (16–104%). Different methods for assessment of clubbing had poor correlation, and as a result, clubbing prevalence varied according to the method used, ranging from 7 to 42% in the total group of patients and 7–52% in IPF. The degree of clubbing did not correlate with FVC or TLCOc (p > 0.2) or with quality of life scores, but lower mean TLCOc scores were seen in patients with clubbing than in those without. Conclusion: Clubbing was present in 7–42% of our fibrotic ILD cohort and showed no correlation with disease severity. Although considered an important clinical feature, assessment methods for clubbing showed no to poor agreement. Further studies are therefore needed to gain more insight into measuring clubbing reliably and the possible prognostic value and evolution of clubbing. Highlights: Clubbing, an important clinical feature, was assessed in patients with fibrotic ILDs. Assessment methods for clubbing showed no to poor agreement. The prevalence of clubbing in fibrotic ILDs ranged from 7 to 42% dependent on the method of assessment. Clubbing showed no correlation with disease severity.